Ferns Vegetation in the Lemor Botanical Garden, Suela District, East Lombok Regency - Tarita Sita Febiana; Ahmad Raksun; I Gde Mertha (Jurnal Biologi Tropis, 2021)
Lemor Botanical Garden is located in Suela Village, East Lombok Regency, West Nusa Tenggara. Various plant exist in the Lemor Botanical Garden. One of them is ferns. Research on the identification of ferns in the Lemor Botanical Garden was carried out from July to September 2020. The purpose of this research was to determine the spesies of ferns in the Lemor Botanical Garden area. This research is a descriptive research. The data was collected by using the sruise method. The results showed that in The Lemor Botanical Garden there were 12 families and 29 spesies of ferns. The spesies of ferns found were: Tectaria angulata, Tectaria melanocaula, Tectaria palmate, Tectaria SP, Pteridrys syrmatica, Nephrolepis cordifolia, Nephrolepis falcate, Stenochlaena palustris, Drynaria quercifolia, Lemmaphyllum carnosum, Adiantum tenerum, Pteris vittata, Pteris ensiformis, Pteris biaurita, Pteris asperula, Cheilanthes tenuifolia, Antrophyum sessilifolium, Elaphoglossum norsii, Diplazium esculentum, Pityrogramma calomelanos, Macrothelypteris torresiana, Spaerostephanos polycarpus, Mesophlebion sp., Pneumatopteris truncate, Amphineuron immersum, Pneumatopteris sp., Microlepia speluncae, dan Asplenium subnormale.